Practising anaesthesia as a community service doctor: a survey-based assessment. (10th April 2017) - Kusel, Belinda; Farina, Zane; Aldous, Colleen
Abstract : Background: Anaesthesia-related maternal mortality remains unacceptably high, especially in district hospitals. Community service doctors (CSDs) play an important role in the provision of anaesthesia in these hospitals. The purpose of this study was to understand the experience of doctors providing anaesthesia during community service. Identifying deficiencies in the performance of anaesthesia by CSDs can lead to remedial actions. Methods: A prospective, questionnaire-based study was done of doctors who had done their anaesthesia rotation during their internship in Pietermaritzburg, between 2008 and 2010. Quantitative data were collected regarding their performance of anaesthesia during community service. The data included details concerning the provision of anaesthesia, supervision and training, and whether CSDs felt adequately prepared to perform anaesthesia during community service. Qualitative data were also collected, which will be reported in another article. Results: The study response rate was 72.9%. Roughly half of the respondents performed anaesthesia during community service, of which two-thirds did more than 50 cases. Obstetric anaesthesia was the most common procedure performed. CSDs worked largely unsupervised, 63% had very little supervision and 62% received no further training in anaesthesia during community service. CSDs felt adequately prepared to administer obstetric anaesthesia, but less well prepared to perform general anaesthesia for appendicectomies and ectopic pregnancies. Discussion: CSDs perform a large proportion of the anaesthesia in rural hospitals, where they work largely unsupervised. Furthermore, CSDs feel less well prepared to perform general anaesthesia than spinal anaesthesia. To meet the needs of patients in these areas, intern training needs to be aimed at improving anaesthesia delivery in rural hospitals and guidelines need to be established regarding the performance of anaesthesia by CSDs. Conclusion: The study showed that CSDs play an important role in provision of anaesthesia services, especially in rural areas. However, they work largely unsupervised and receive little further training or support. A large proportion do not feel comfortable in administering general anaesthesia. Intern training should be adjusted to meet the needs of CSDs.